Social media hype in times of crises: Nature, characteristics and impact on organizations - PANG, Augustine (Institutional Knowledge at Singapore Management University, 2013)
This article extends Vasterman’s (2005) concept of media hype by analyzing how it applies in the social media context. It then develops the concept of social media hype, its nature, characteristics through examination of five cases that attracted much social media attention. Social media hype can be defined as a netizen-generated hype that causes huge interest that is triggered by a key event and sustained by a self-reinforcing quality in its ability for users to engage in conversation. It involves a trigger event, followed by interest waves, and sustaining of the interests on different social media platforms. In response, organizations should pay heed to rigorously monitored sentiments online, respond quickly in the same medium in which the hype occurs, sharing consistent message across all mediums, and most importantly, value relationships with stakeholders.